2012
DOI: 10.1128/iai.06180-11
|View full text |Cite
|
Sign up to set email alerts
|

Free Lipid A Isolated from Porphyromonas gingivalis Lipopolysaccharide Is Contaminated with Phosphorylated Dihydroceramide Lipids: Recovery in Diseased Dental Samples

Abstract: Recent reports indicate that Porphyromonas gingivalis mediates alveolar bone loss or osteoclast modulation through engagement of Toll-like receptor 2 (TLR2), though the factors responsible for TLR2 engagement have yet to be determined. Lipopolysaccharide (LPS) and lipid A, lipoprotein, fimbriae, and phosphorylated dihydroceramides of P. gingivalis have been reported to activate host cell responses through engagement of TLR2. LPS and lipid A are the most controversial in this regard because conflicting evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
(75 reference statements)
0
28
0
Order By: Relevance
“…endodontalis , including the recently characterized serine lipid termed “Lipid 654” (11). Of note, Figure 1A shows that the total lipid extracts or HPLC fractionated lipids of P. endodontalis did not contain common lipid A components characteristic of P. gingivalis LPS (17). …”
Section: Resultsmentioning
confidence: 99%
“…endodontalis , including the recently characterized serine lipid termed “Lipid 654” (11). Of note, Figure 1A shows that the total lipid extracts or HPLC fractionated lipids of P. endodontalis did not contain common lipid A components characteristic of P. gingivalis LPS (17). …”
Section: Resultsmentioning
confidence: 99%
“…Significant differences in stimulation potency between 33277 LPS and ⌬1773⌬1587 LPS (P Ͻ 0.01) were observed for TLR4 but not for TLR2, TLR2/TLR1, and TLR1 activation at each concentration tested. assisted laser desorption ionization-time of flight) analysis (20) and was recently reported to contain phosphorylated dihydroceramides as well (49). Figure 6a demonstrates that the aqueous phase stimulates TLR2/TLR1 potently.…”
Section: Fig 4 P Gingivalis Lipid a Structure Affects Tlr4 Activatiomentioning
confidence: 99%
“…TLR2 is reported to be activated by many other microbial products, including phenol-soluble modulins (3) and Porphyromonas gingivalis lipoprotein (4), lipopolysaccharide (LPS) (5-7), and fimbriae (8-10). However, two recent reports have questioned the extent to which lipoprotein, LPS, or fimbriae mediate TLR2 engagement by P. gingivalis (11,12).We previously reported that the total lipid extract of P. gingivalis promotes activation of mouse dendritic cells and inhibits osteoblast-mediated bone deposition through engagement of TLR2 (13,14). These effects were attributed to the dominant phosphorylated dihydroceramide lipids of P. gingivalis, in particular, phosphoethanolamine dihydroceramides.…”
mentioning
confidence: 99%
“…TLR2 is reported to be activated by many other microbial products, including phenol-soluble modulins (3) and Porphyromonas gingivalis lipoprotein (4), lipopolysaccharide (LPS) (5-7), and fimbriae (8-10). However, two recent reports have questioned the extent to which lipoprotein, LPS, or fimbriae mediate TLR2 engagement by P. gingivalis (11,12).…”
mentioning
confidence: 99%